Not a single orchid... - Zelenko, Harry (Universidad de Costa Rica, 2015)
We all know that the original intent of the Convention on International Trade in Endangered Species was for the protection of animals. Adding flora was an afterthought that seemed like a good idea at the time. But it has gotten out of hand, and CITES regulation is now deeply entrenched worldwide caus- ing unnecessary expense, heartache and aggravation, not to mention contributing to corruption, smuggling and who knows what else. But I sincerely believe that CITES has not saved one plant from extinction since its inception.